The use of modals in academic discourse: A comparative analysis - Chong S.T.; Ng Y.J.; Karthikeyan J.; Lee S.Y. (American Institute of Physics Inc., 2024)
This paper examines the use of the modal auxiliary verb in scientific and non-scientific writing. The purpose of this study is to investigate that modal auxiliary verb plays an imperative role in the writing of scientific reports. The modal auxiliary verb has many roles in predicting, commanding, suggesting, and other roles. Good command of the knowledge about modal auxiliary verb helps a science writer in his or her writing. This is very important for their projects, dissertation, reports, journal publications, and more. The corpus studied is the Lancaster-Oslo/Bergen Corpus (LOB). We utilized the Oxford Wordsmith Tools Version 8 as the methodology. The finding shows that would is the most popular modal verb across genres and shall is the least popular one. This also indicates that different genres prescribe different writing styles and influence the usage of the modal auxiliary verb. 2023 Author(s).